Managing Digital Transformation in Marketing: "Fusion of Traditional Marketing and Digital Marketing" - Ankur Singh Bist; Vertika Agarwal; Qurotul Aini; Nimatul Khofifah (International Transactions on Artificial Intelligence, 2022)
This paper aims to go deeper into how a firm executes digital transformation in marketing. The experiences discussed in this article will give insight from a business practice standpoint. The difficulties encountered and the solutions proposed will broaden knowledge and inspire additional research. This paper employs a qualitative technique, with one of Indonesia's significant telecommunications companies serving as the primary case study. Semi-structured interviews were used in this study, with 25 interviews conducted at the senior management level. As a result, this organization is developing digital transformation through digital and traditional marketing. A big challenge is focusing on existing consumers through conventional marketing while reaching out to additional customers through digital marketing. One of the aspects to consider while designing digital technology is the digital divide in some nations.